Abscisic acid alleviates chilling injury in cold-stored peach fruit by regulating ethylene and hydrogen peroxide metabolism - Tang, Jixing; Zhao, Yaoyao; Qi, Shuning; Dai, Qi; Lin, Qiong; Duan, Yuquan (Frontiers in Plant Science, 2022)
Peach (Prunus persica (L.) Batsch) fruit are vulnerable to chilling injury if they are exposed to unsuitable low temperatures conditions. It has been shown that abscisic acid (ABA) can alleviate chilling injury, but its mechanism is not clear. To evaluate its effectiveness and mechanism in alleviating chilling injury during cold storage, exogenous ABA was applied to peach fruit by immersion in 100 μmol L-1 solutions for 10 minutes. In our experiment, ABA alleviated chilling injury symptom development while reducing H2O2 content and the production of ethylene. In addition, ABA also inhibited the expression of the ethylene synthesis related genes ACO1 and EIN2. At the same time, ABA treatment significantly regulated the enzymatic antioxidant pathway and the ascorbate-glutathione (AsA-GSH) cycle. The abundance of the transcripts encoding these enzymes activities also changed correspondingly. These results suggest that ABA may alleviate chilling injury by reducing the stress response to chilling as shown by inhibition of stress ethylene production and scavenging of stress-related H2O2 via the antioxidant enzyme and AsA-GSH pathways.